Analisis Wacana Kritis Film Minggu Pagi di Victoria Park - , SUJADMI, Prof.Dr.Sunyoto Usman ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The topic of violence against Indonesian Women Migrantâs Worker (Tenaga Kerja Indonesia/ TKI) who worked as households-helper has been unsolving issue commonly. The purpose of this study is to find the meaning in the movie as a tool for constructing the discource of âPahlawan Devisaâ and the govermentâs responsibility as well. This study based on the movie of Sunday Morning in Victoria Park (Minggu Pagi di Victoria Park) which is directed by Lola Amaria and released in June 2010. This study uses qualitative critical discourse analysis by Norman Fairclough. The analysis cover text, practical discursive and socio-culture. Continously, this study involve some audienceâs responses from any mass-media randomly. The results of this study illustrates that the movie of Sunday Morning in Victoria Park just narrates positive stories about the Indonesian Women Migrantâs Worker. It movie do not tell about the real condition of the Indonesian Women Migrantâs Worker such as violence or persecution and death-law. Unfortunately, the director just want to be neutral without creating judgements to goverment or the womenâs labour clearly. Strongly, this movie emphasizes about the heroism of the Indonesian Women Migrantâs Worker that is still being controversy issue until now. The most dominant factor influencing to be migrant workers is financial, especially for raising their economics aspects. Movie is not independent thing. There is ideology as the background of it. Moreover, movie also can be medium for making people as comodities. Sunday Morning in Victoria Park tries to get attention of the audiences by using migrant workersâ story in Hongkong. As their expectations, this movie could get positive acceptance by public while thereâre so many horor movie which telling about women sexuality commercially. The similarity of this movie with others is women as the object of the story. The main different of this movie with others lies on the focus of women as a hero and does not explore their sexualty. The conclusion of this study is goverment, mass-media, and family as the three elements that influence in creating and keeping the discourse of heroism as women migrantâs worker. There is the role of mass-media to hide the domination and hegemony of the goverment and the family towards women migrantâs worker. The power relation has a role in producing a space to be women migrantâs worker which is done by the goverment. It can be seen by the institutions and the policies that are for preserving the heroismâs discourse and also a term of comodification from it discourse. In another side, mass-media has a big power to spread discourses until it can be accepted by public as well.